(untitled) - Ondrus, Jan; Palo, Jozef (Doprava a spoje, 2012)
Currently in many countries come to the high increase of number of motor vehicles. Such increase brings also many problems which arise in particular in residential areas and on roads out of residential areas since they are not able to ensure reliable and continuous traffic on these roads. This paper presents the analysis and issue of motorization rate comparison in particular district of the Slovak Republic. It works with available data of particular years.